Analysis of Moral Message in “Buzz” Album by Niki Zefanya - Windy Ainiyah Putri (Politeknik Negeri Sriwijaya, 2025)
ABSTRACT: This study explores the moral messages found in the lyrics of the Buzz album by Niki Zefanya, an Indonesian singer who writes and performs in English. The album contains 13 songs, each filled with emotional and reflective content that offers listeners insights into life, relationships, and personal growth. This research employs a qualitative method with a moral criticism approach to analyse how Niki communicates values such as empathy, resilience, and self-awareness through figurative language and storytelling. The data were collected by carefully listening to each song while reading the lyrics and examining the feelings or conditions of the author when writing the song. The collected data were analysed using Narrative Analysis for Moral Values, identifying stories, emotions, and cultural contexts within the lyrics to uncover and categorize moral themes. The findings show that, although the messages are not stated directly, they can be felt and understood through careful interpretation. This study aims to help listeners, especially non-native English speakers, understand the deeper meanings behind English song lyrics and encourage more thoughtful listening experiences. Keywords: Buzz album, Niki Zefanya, moral message, song analysis DOI: https://doi.org/10.5281/zenodo.18253474